Impact of Beliefs About Atlantic Tropical Cyclone Detection on Conclusions About Trends in Tropical Cyclone Numbers - Tokdar, Surya T.; Grossmann, Iris; Kadane, Joseph B.; Charest, Anne-Sophie; Small, Mitchell J. (Bayesian Analysis, 2011)
Whether the number of tropical cyclones (TCs) has increased in the last 150 years has become a matter of intense debate. We investigate the effects of beliefs about TC detection capacities in the North Atlantic on trends in TC numbers since the 1870s. While raw data show an increasing trend of TC counts, the capability to detect TCs and to determine intensities and changes in intensity has also increased dramatically over the same period. We present a model of TC activity that allows investigating the relationship between what one believes about the increase in detection and what one believes about TC trends. Previous work has used assumptions on TC tracks, detection capacities or the relationship between TC activity and various climate parameters to provide estimates of year-by-year missed TCs. These estimates and the associated conclusions about trends cover a wide range of possibilities. We build on previous work to investigate the sensitivity of these conclusions to the assumed priors about detection. Our analysis shows that any inference on TC count trends is strongly sensitive to one's specification of prior beliefs about TC detection. Overall, we regard the evidence on the trend in North Atlantic TC numbers to be ambiguous.